PROCESS FOR PREPARING MULTILAYERS WITH AN ORDERED MESOPOROUS STRUCTURE, MATERIAL OBTAINED IN THIS MANNER, AND USE - SOLER ILLIA, GALO JUAN DE AVILA ARTURO; MIGUEZ GARCIA, HERNAN RUY; FUERTES, MARIA CECILIA (2011)
The subject matter of the invention is a simple and reliable process for producing multilayers formed by thin mesoporous films of oxides or oxide or hybrid organic/inorganic materials by means of a combination of sol-gel methods, selfassembly of surfactants and selective functionalization of the surfaces od the pores. Each one of the constituent layers has a chemical composition, thickness and index of refraction.